ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAYANAN PADA PERUSAHAAN UMUM DAERAH (PERUMDA) MUARA TIRTA KOTA GORONTALO - Lutfi Madjid; Deby R. Karundeng; Moh. Afan Suyanto (Bisnis-Net, 2023)
This study aims to analyze the factors that influence the quality of service at the Regional Public Company (Perumda) Muara Tirta, Gorontalo City. The sample that was used as the research target was parties related to service quality at the Muara Tirta Regional Public Company (Perumda) in Gorontalo City, totaling 101 people, and all of them became respondents. The method used is a quantitative method using multiple linear regression. Based on the test results, it shows that the variable customer quality has a positive and significant effect on service quality, professional quality has a negative and insignificant effect on service quality, management quality has a positive and significant effect on service quality, and simultaneously customer quality, professional quality, and management quality simultaneously simultaneous positive and significant effect on service quality